Maternal History and Uterine Artery Doppler in the Assessment of Risk for Development of Early- and Late-Onset Preeclampsia and Intrauterine Growth Restriction. (22nd April 2009) - Llurba, Elisa; Carreras, Elena; Gratacós, Eduard; Juan, Miquel; Astor, Judith; Vives, Angels; Hermosilla, Eduard; Calero, Ines; Millán, Pilar; García-Valdecasas, Bárbara; Cabero, Lluís
Abstract : Objective . To examine the value of one-step uterine artery Doppler at 20 weeks of gestation in the prediction pre-eclampsia (PE) and/or intrauterine growth restriction (IUGR). Methods . A prospective multicentre study that included all women with singleton pregnancies at 19–22 weeks of gestation (w). The mean pulsatility index (mPI) of both uterine arteries was calculated. Receiver-operating characteristics curves (ROC) were drawn to compare uterine artery Doppler and maternal risk factors for the prediction of early-onset PE and/or IUGR (before 32 w) and late-onset PE and/or IUGR. Results . 6, 586 women were included in the study. Complete outcome data was recorded for 6, 035 of these women (91.6%). PE developed in 75 (1.2%) and IUGR in 69 (1.1%) cases. Uterine Doppler mPI was 0.99 and the 90th centile was 1.40. For 10% false-positive rate, uterine Doppler mPI identified 70.6% of pregnancies that subsequently developed early-onset PE and 73.3% of pregnancies that developed early-onset IUGR. The test had a lower detection rate for the late-onset forms of the disease (23.5% for PE and 30% for IUGR). Maternal history has a low sensitivity in the detection of early-onset cases, although it is better at detecting late-onset PE. Conclusion . Uterine artery Doppler and maternal risk factors seem to select two different populations - early and late-onset PE which might suggest a different pathogenesis.